Students’ Difficulties in Writing Descriptive Text at the Seventh Grade of SMP Sint Carolus Bengkulu - Nelly Kristiana; Wisma Yunita; Syahrial Syahrial (Linguists : Journal Of Linguistics and Language Teaching, 2021)
The objective of this research was to investigate the students’ difficulties in writing descriptive text, the most dominant difficulty faced by the students, and the students’ strategies to overcome these difficulties. This study was conducted at the Seventh Grade of SMP Sint Carolus Bengkulu. This is a descriptive quantitative study. The instruments used in this research were questionnaire and interview. Based on the results, it was found that students experienced difficulties in the three aspects of the study, namely linguistic, psychological, and cognitive difficulties. In each of these aspects, organization is the highest one followed by behaviour, feedback, grammatical items, and vocabulary. In organizations, difficulties in developing ideas are the most difficult. Anxiety is the highest difficulty in behaviour, while the lack of practice is the most difficulty in the feedback. The difficulty in using connectors is the highest point in the grammatical items, and the lack of vocabulary is the most difficulty in the vocabulary. Based on the questionnaire and interview results, organization was the most difficult aspect in writing descriptive text. To overcome the difficulties, the students choose to master vocabulary and learning from other sources such as books or the internet while the others like to read from dictionary. Finally, it is also suggested for other researchers to carry out similar research in a broader scope, as well as a description, especially about the mechanic that get negative results.